EFEKTIVITAS PENDIDIKAN KESEHATAN MENGGUNAKAN VIDEO TERHADAP KEPATUHAN PEMBATASAN CAIRAN PADA PASIEN HEMODIALISA DI KLINIK PANDAONI MEDIKA JAKARTA - Azzahra, Maulyda; Herlina, Santi (Fakultas Ilmu kesehatan UPN Veteran Jakarta, 2024)
Chronic kidney disease is a metabolic disease that can be seen in a decrease in kidney function. Patients with chronic kidney failure who do hemodialysis have a lot of fluid overload problems that cause an increase in IDWG. Patients who have excess fluids need to limit fluids. One effort to increase adherence is to provide education in advance to increase knowledge about the disease by providing health education using video. The purpose of this study was to determine the effectiveness of health education using video on compliance with fluid restrictions in hemodialysis patients at the Klinik Pandaoni Medika Jakarta. This study used a quantitative approach with a quasi-experimental design with two control groups for pre- and post-tests. The sampling technique used was purposive sampling on a total sample of 78 respondents. The analysis used is a paired sample t-test and an independent t-test. After the intervention was carried out and the results obtained, the intervention group experienced an average decrease indicating the influence of health education using video (p = 0.000), while in the control group the average compliance value increased with a value of p = 0.002, which indicated the influence of health education using video with a bad influence on the level of adherence to fluid restriction in the control group. There were differences in adherence to fluid restriction in the intervention group and the control group (p = 0.000).